Prevalence of malaria parasitaemia in school-aged children and pregnant women in endemic settings of sub-Saharan Africa: A systematic review and meta-analysis. (November 2020) - Makenga, Geofrey; Menon, Sonia; Baraka, Vito; Minja, Daniel T.R.; Nakato, Swabra; Delgado-Ratto, Christopher; Francis, Filbert; Lusingu, John P.A.; Van Geertruyden, Jean-Pierre
Abstract: Despite increased malaria control efforts, school-aged children (5–14 years) have higher a malaria prevalence compared to children under-five. In high-transmission settings, up to 70% of school-aged children harbour malaria parasitaemia and therefore contribute significantly to the reservoir for transmission. A systematic review was performed to explore the correlation between the malaria parasite carriage in pregnant women and school-aged children living in similar endemic settings of sub Saharan Africa to inform strategies to improve targeted malaria control. In order to obtain data on malaria prevalence in pregnant women and school-aged children living in the same endemic setting, we searched the Malaria in Pregnancy Library, PubMed, Cochrane library and Web of Science in December 2018. We fit a fixed effect model to obtain a pooled risk ratio (PRR) of malaria in school-aged children versus pregnant women and used Poisson regression to estimate risk ratios in school-aged children for every increase in prevalence in pregnant women. We used data from six (out of 1096) sources that included 10 data points. There was a strong linear relation between the prevalence of malaria infection in pregnant women and school-aged children ( r  = 0·93, p  < 0·0001). School-aged children were nearly twice at risk to carry parasites compared to pregnant women (RR = 1.95, 95% CI: 1·69–2.25, p  < 0.01). Poisson regression showed that a 1% increase in prevalence of malaria infection in pregnant women was significantly associated with increase in risk in school-aged children by 4%. Malaria infection prevalence in school-aged children is strongly correlated with the prevalence in pregnant women living in the same community, and may be considered as alternative indicators to track temporal and spatial trends in malaria transmission intensity. Chemoprevention strategies targeting school-aged children should be explored to reduce malaria burden and transmission in school-aged children and its potential impact on communities. Graphical abstract: Fig. 5 Scatter plot with Pearson correlation coefficient of malaria parasitaemia in pregnant women and school-aged children living in a common setting, sub Saharan Africa Unlabelled Image